1982
DOI: 10.1007/bf00255956
|View full text |Cite
|
Sign up to set email alerts
|

Collagenase for Peyronie's disease experimental studies

Abstract: This pilot study was designed to test the feasibility of using purified clostridial collagenase in the clinical management of Peyronie's disease. The basic properties of this agent are discussed. We studied its effect on Peyronie's plaque tissue by a quantitative in vitro assay utilising the liberation of free alpha-amino groups as an index of enzymatic collagenolysis. Tissue from three patients with Peyronie's disease was used. Tunica albuginea from a second group of three normal patients was studied in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0
5

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(68 citation statements)
references
References 15 publications
1
62
0
5
Order By: Relevance
“…This selectivity results in the reduction of PD plaques without damage to surrounding elastic tissue, vascular smooth muscle or axon myelin sheaths [13][14][15]. Early clinical studies indicated the potential for CCH to be used for the treatment of patients with PD [16][17][18][19], with one phase IIb study demonstrating the benefit of penile modelling in conjunction with intralesional CCH [19].…”
Section: Pharmacodynamic Properties Of Cchmentioning
confidence: 96%
“…This selectivity results in the reduction of PD plaques without damage to surrounding elastic tissue, vascular smooth muscle or axon myelin sheaths [13][14][15]. Early clinical studies indicated the potential for CCH to be used for the treatment of patients with PD [16][17][18][19], with one phase IIb study demonstrating the benefit of penile modelling in conjunction with intralesional CCH [19].…”
Section: Pharmacodynamic Properties Of Cchmentioning
confidence: 96%
“…The therapeutic potential of collagenase was initially introduced more than two decades ago in both in vitro and in vivo studies by Gelbard et al [34][35][36]. Although not placebo-controlled, a recent study employing two intralesional collagenase injections over three injection cycles significantly decreased plaque size and penile curvature in men with PD [37].…”
Section: Collagenasementioning
confidence: 97%
“…Use of collagenase for PD was first described by Gelbard in 1982, in which collagenase was injected into PD plaques removed from patients and studied in vitro. 33 In 1985, Gelbard performed the first human trials. 34 Intralesional collagenase injection of clostridial collagenase has demonstrated true efficacy with a significant decrease in penile curvature, plaque size and an improvement in PD symptom bother scores in multiple trials.…”
Section: Topical Electromotive Therapy (Iontophoresis) With Verapamilmentioning
confidence: 99%